2016
DOI: 10.2147/ppa.s103057
|View full text |Cite
|
Sign up to set email alerts
|

How payment scheme affects patients' adherence to medications? A systematic review

Abstract: BackgroundA previous systematic review reported that increase in patients’ medication cost-sharing reduced patients’ adherence to medication. However, a study among patients with medication subsidies who received medication at no cost found that medication nonadherence was also high. To our knowledge, no study has evaluated the influence of different medication payment schemes on patients’ medication adherence.ObjectiveThis study aims to review research reporting the influence of payment schemes and their asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 32 publications
(60 reference statements)
0
28
0
Order By: Relevance
“…In addition to the 15 newly identified relevant SRs, six SR of the previous overview were included. Finally, 21 SRs were included in this overview [2040]. The process of study selection is illustrated in the PRISMA flowchart [41] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the 15 newly identified relevant SRs, six SR of the previous overview were included. Finally, 21 SRs were included in this overview [2040]. The process of study selection is illustrated in the PRISMA flowchart [41] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In another study in the United States, patients with an overactive bladder who received subsidised medications had a similarly low adherence rate, at only 34% [ 15 ]; this rate, notably, did not differ significantly from those in previous studies for patients with a co-payment scheme (30.3–53%) [ 15 ]. The above-mentioned systematic study further confirmed that medication adherence among patients with medication subsidies (i.e., the cost of medication was minimal or free) was similar to that of patients with other payment schemes [ 7 ]. Although there are numerous studies on the medication adherence rate among patients with medication subsidies, the reasons for the non-adherence in this population remains unexplored.…”
Section: Introductionmentioning
confidence: 78%
“…Besides medication costs, drug benefit caps and higher co-payments were also reported as reasons for medication non-adherence [ 5 , 6 ]. A systematic review of the influence of patients’ payment scheme on medication adherence showed that a reduction in patient cost-sharing—such as lower co-payment and higher drug coverage and prescription caps—were associated with better medication adherence [ 7 ]. Patients who reported that they were non-adherent (including skipping doses, stopping taking a prescription drug altogether, or failing to fill a new prescription) due to medication costs did so because they either lacked the money or wanted to save money [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review looking at how different payment schemes affected medication adherence reported that not only the amount of money spent for medications but also the perceived financial burden of medications could influence adherence. 32 Thus, patients’ concerns relating to the cost of medications need to be carefully gauged, and their possible impact on adherence assessed.…”
Section: Discussionmentioning
confidence: 99%